Chinese Aid and Local Ethnic Identification - Ann-Sofie Isaksson (Research Institute of Industrial Economics (IFN), 2020)
Recent empirical evidence suggests that Chinese development finance may be particularly prone to elite capture and patronage spending. If aid ends up in the pockets of political elites and their ethno-regional networks, this may exacerbate ethnic grievances and contribute to ethnic mobilization. The present paper examines whether Chinese development projects make local ethnic identities more salient in African partner countries. A new geo-referenced dataset on the subnational allocation of Chinese development finance projects to Africa is geographically matched with survey data for 50,520 respondents from 11 African countries. The identification strategy consists in comparing sites where a Chinese project was under implementation at the time of the interview to sites where a Chinese project will appear subsequently. The empirical results indeed suggest that living near an ongoing Chinese project makes ethnic identities more salient. There is no indication of an equivalent pattern when considering development projects of other donors.
Keywords: F35; O19; O55; 330; China; Aid; Ethnic identities; Africa